The use of mobile devices for learning Italian as a FL in informal settings: a quantitative study: uno studio quantitativo - Averna, Carmelo (Cuadernos de Filología Italiana, 2022)
Starting from the learner’s point of view, we carried out an analysis aimed at investigating the use, interest, and utility of mobile devices for the in-depth study of Italian as a FL in informal settings. The participants in the survey were students of Italian as a FL with different personal characteristics and diverse levels of language proficiency. This exploratory study was aimed at examining the following four matters: 1) The extent of usage of language learning apps among students of Italian as a FL; 2) The degree of satisfaction with the experience of the app as a language learning resource; 3) The correlation between the use of the apps and the level of language proficiency; 4) The correlation between the use of the apps and the age of the respondents. In view of the objectives of this study, we made use of an essentially quantitative methodology. The data collected provided interesting insights that led us to reflect on the demographic attributes and the level of interest and satisfaction of the learners of Italian as a FL, and their disposition to resort to mobile devices as learning tools.
Keywords: mobile applications; informal learning; Italian as a FL; Mobile Learning; ICT